Software ubuntu y su efecto en el desarrollo educativo en los estudiantes del primer año de bachillerato de la Unidad Educativa Eugenio Espejo año 2016 - Castro Pérez, Juan Fernando (2016)
Due to the increasing development experienced by the Free Software in education, that has enabled new ways of imparting knowledge and introduces students and teachers to innovative processes in their own education. Therefore, the objective of this research was to analyze the use of free software as a support tool in the teaching-learning process in Teleinformatic Engineering career of the EUGENIO ESPEJO. In methodology, the technique used for the collection of information was the survey. Fieldwork was then performed to obtain the information of students and teachers of the career Teleinformatic Engineering. The information collected was reflected in the analysis and discussion of results, in which it was determined that it is necessary to make the proposal that is presented at the end of the investigation; in order to respond to the challenge that Higher Education Institutions face today, must have a vision and a new paradigm in training their students and have a flexible computing infrastructure to develop new learning experiences according to the society of knowledge